2012
DOI: 10.1152/ajprenal.00359.2012
|View full text |Cite
|
Sign up to set email alerts
|

Activated CD47 regulates multiple vascular and stress responses: implications for acute kidney injury and its management

Abstract: Ischemia-reperfusion injury (IRI) remains a significant source of early and delayed renal transplant failure. Therapeutic interventions have yet to resolve this ongoing clinical challenge although the reasons for this remain unclear. The cell surface receptor CD47 is widely expressed on vascular cells and in tissues. It has one known soluble ligand, the stress-released matricellular protein thrombospondin-1 (TSP1). The TSP1-CD47 ligand receptor axis controls a number of important cellular processes, inhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 99 publications
3
46
0
Order By: Relevance
“…The dual KD of CD47 and TGFB1 likely works through the perturbation of the interaction of both proteins with the secreted protein, thrombospondin 1 (TSP1). TSP1 is a direct binding partner of CD47 and has been shown to inhibit angiogenesis, modulate extracellular matrix formation and cell migration, suppress to tumor, and most importantly, activate latent TGFB1 [45, 46]. Thus, a reduction in CD47 on the cell surface of cells allows for higher micro environmental levels of TSP1, potentially leading to the activation of more TGFB1, which has been directly shown in murine osteoblasts [44].…”
Section: Discussionmentioning
confidence: 99%
“…The dual KD of CD47 and TGFB1 likely works through the perturbation of the interaction of both proteins with the secreted protein, thrombospondin 1 (TSP1). TSP1 is a direct binding partner of CD47 and has been shown to inhibit angiogenesis, modulate extracellular matrix formation and cell migration, suppress to tumor, and most importantly, activate latent TGFB1 [45, 46]. Thus, a reduction in CD47 on the cell surface of cells allows for higher micro environmental levels of TSP1, potentially leading to the activation of more TGFB1, which has been directly shown in murine osteoblasts [44].…”
Section: Discussionmentioning
confidence: 99%
“…CD47 is activated by TSP1 to produce a series of biological effects, including regulation of inflammation, cell adhesion, self-recognition, limitation of cell and animal survival in response to various stressors, and regulation of blood pressure, among other things [11,30,31]. Activation of CD47 by TSP1 inhibits the effects of the NO pathway via limitation of eNOS activity through suppression of calcium flux [32].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
“…TSP1 engages CD47 via binding to its C-terminal domain and thus limits the downstream effects of the eNOS/NO signaling cascade [11]. Bauer et al reported that both TSP1 and CD47 are significantly upregulated in vascular cells during states of ischemia [12].…”
Section: Introductionmentioning
confidence: 99%
“…CD47, along with ligands thrombospondin-1 (TSP-1) and SIRPα, is involved in numerous physiological and pathological processes including cell spreading, platelet activation, chemotaxis, adhesion, extracellular matrix organization, signaling, survival, proliferation, apoptosis, migration and ischemia-reperfusion injury (reviewed in [2628]). A potential role for CD47 in AD has also been identified with studies reporting CD47 participation in the microglial proinflammatory response to, and uptake of, fibrillar Aβ [2931].…”
Section: Introductionmentioning
confidence: 99%